Observation of emergent momentum–time skyrmions in parity–time-symmetric non-unitary quench dynamics - Kunkun Wang (Nature Portfolio, 2019)
Dynamic topological phenomena remain challenging to be probed experimentally. Here, Wang et al. theoretically characterize and experimentally detect dynamical skyrmions in parity‐time‐symmetric non‐unitary quench dynamics in single‐photon discrete‐time quantum walks.